Polymorphism of the human complement C4 and steroid 21-hydroxylase genes. Restriction fragment length polymorphisms revealing structural deletions, homoduplications, and size variants. - Schneider, P M (1986)
Several autoimmune disorders as well as congenital adrenal hyperplasia (CAH) are either associated or closely linked with genetic variants of the fourth component of complement (C4A and C4B) and the enzyme steroid 21-hydroxylase (21-OH). These proteins are encoded by genes that are located downstream from the genes for complement proteins, C2 and factor B (BF) between HLA-B and -DR in the major histocompatibility complex (MHC). Previous studies of variants and null alleles were based on electrophoretic mobility of C4 protein and linkage with disease phenotypes. These data did not permit analysis of the basis for the observed null alleles and duplicated variants. We studied this region of the MHC in 126 haplotypes for a structural analysis of the four adjacent loci, C4A, 21-OHA, C4B, and 21-OHB. About half of the C4 genes typed as C4 null are deleted and several unrecognized homoduplicated C4 alleles were detected. Hence the frequencies of different C4 structural variants must be recalculated based on a direct analysis of the genes. Analysis of the C4/21-OH genes of patients with the classical (salt-wasting) form of CAH showed that some involve a deletion of the C4B and 21-OHB genes; whereas for two only the 21-OHB gene is deleted, i.e., the C4B gene is present. Together, these data provide a better understanding of the mechanisms generating and importance of deleted C4 and 21-OH null alleles in human disease.